2015
DOI: 10.4067/s0718-40262015000500005
|View full text |Cite
|
Sign up to set email alerts
|

Inducción De Tolerancia en Modelo De Autotrasplante

Abstract: induction of tolerance in allogeneic transplant model introduction: Vascularized composite allotransplantation (VCA) involves the transplantation of complex anatomical structures including different kinds of tissue. The aim was to study the effect of a treatment with immature dendritic cells in a model of VCA. materials and methods: The rat hind limb allotransplantation model was used. Due to the high antigenic mistmatch Brown norway rats were used as donors and Lewis rats as recipients. The bone marrow derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The mosquito microbiota is diverse; mosquito-microbe associations have been reported with bacteria, fungi, viruses and protists [2][3][4][5]. The gut is the main site of colonization, but microbial associations with other tissues, such as salivary glands and reproductive organs, have also been reported (table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mosquito microbiota is diverse; mosquito-microbe associations have been reported with bacteria, fungi, viruses and protists [2][3][4][5]. The gut is the main site of colonization, but microbial associations with other tissues, such as salivary glands and reproductive organs, have also been reported (table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Protists (e.g. Ascogregarina) and viruses found in mosquitoes are beyond the scope of this review and are described or reviewed elsewhere [2,3]. The identities of Aedes midgut microbes have been studied in the context of a wide range of factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the pioneering studies of Pecoraro and Chianelli on the reactivity of transition metal sulfides [47] . However, multiple studies have shown that when metallic phases are tested under standard hydrodesulfurization conditions, part of their structure remains in a reduced state and that sulfidation is partly reversible [48–55] . Therefore, reduced metallic moieties can act as active sites for hydrodesulfurization.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos que avaliaram o perfil econômico de estudantes de Odontologia de uma universidade particular e de três universidades do Sudeste do país encontraram uma renda familiar média-alta, o que discorda o encontrado neste estudo. Embora a universidade de estudo seja também particular, acredita-se que tal discordância se dê pelo motivo da mesma se localizar no interior de um estado da região Nordeste, visto que, as discrepâncias econômicas entre as regiões são reais e notórias(SEMENOFF et al, 2015;LOFFREDO et al, 2013;MARTINEZ;MIOTTO, 2007).Gráfico 2 -Renda mensal familiar.Quando indagados sobre a doença COVID-19, 75,3% (n = 64) dos acadêmicos afirmaram não terem tido a doença e 24,7% (n = 21) destes já haviam sido contaminados (Gráfico 3). O isolamento social como estratégia para diminuição da vulnerabilidade em relação à COVID-19 já foi confirmado em estudos prévios e a inserção da modalidade de ensino remoto tornou-se necessário desde o início da pandemia para que este isolamento pudesse ser assegurado(GRASSLY et al, 2020).…”
unclassified